Multi-energy scheduling using a hybrid systems approach - Krishnan, Ashok (2018)
This paper presents a mixed logical dynamical (MLD) approach for modelling a multi-energy system. The electrical and thermal energy streams are linked through the operation of combined cycle power plants (CCPPs). The MLD approach is used to develop detailed models of the gas turbines (GTs), steam turbines (STs) and boilers. The power trajectories followed by the GTs, STs and boilers during various start-up methods are also modelled. The utility of the developed model is demonstrated by formulating and solving an optimal scheduling problem to satisfy both electrical and thermal loads in the system. The cost benefit of including flexible loads in the scheduling problem formulation is demonstrated through suitable case studies.